Efikasi Bioinsektisida Beauveria bassiana (Bals.) Vuill Terhadap Gryllus bimaculatus De Geer (Orthoptera: Gryllidae) Pada Padi Ratun - Soleha Soleha; Siti Herlinda; Suparman Suparman (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Soleha, et al. Efficacy of Bioinsecticide from Beauveria bassiana (Bals.) Vuill on Gryllus bimaculatus De Geer (Orthoptera: Gryllidae) on Ratooning Rice in Fresh Swamps. JLSO 5(2):189-197. The use of chemical insecticide to control pest of crop often causes the bad impact on nontarget organisms. B. bassiana is an entomopathogenic fungi has depeloved to control pest of crop as chemical insecticide alternative. This study aimed to measure mortality and damages rate by crickets to rice of the applications of bioinsecticide containing B. bassiana. The Method of this study used Random Block Designs with 5 treatments and 4 replications. The treatments applications were 1 L.ha-1, 2 L.ha-1, 3 L.ha-1, commercial B. bassiana as recommended, and 0 L.ha-1 as control. The applications bioinsecticide containing B. bassiana was significant to nymph of crickets mortality. Mortality of nymph of the applications of B. bassiana was significant with nontreatment (0 L.ha-1). The highest mortality was found in the Bb 3 L .ha-1 about 52,50% and the lowest mortality on 0 L.ha-1. The shortest LT50 was occurred in Bb 3 L.ha-1 about 7,00 days, while the longest LT50 occurred in Bb 0 L.ha-1 about 50,47 – 64,80 days. The highest damages was found in Bb 0 L.ha-1 about 11,55% - 34,14% and the lowest damages was found in Bb 3 L.ha-1 about 5,94 % - 19,82%. Application bioinsecticide containing B. bassiana is significant to crickets mortality and will make an important contribution to the biological control for insect pests.